An Investigation Into Stylistic Devices In The Coaches’ Comments In The Television Shows “The Voice Us” And “The Voice Vietnam” In 2012 - Phạm Trần Hồng Diễm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study is an attempt to find out the coaches’ comments in The Voice US and The Voice Vietnam in 2012. The data for analysis in this thesis are 600 examples of coaches’ comments (300 examples in English and 300 examples in Vietnamese). All examples collected from English and Vietnamese TV shows. The research is carried out based on the combination of a variety of methods namely qualitative, quantitative, statistics, descriptive, analytic, synthetic, comparative, contrastive and inductive. The study focuses on finding out the similarities and differences between the coaches’ comments in the above programs in terms of SDs. I found the similarities and differences in terms of simile, metaphor, rhetorical question, hyperbole, repetition and irony in the coaches’ comments in the television shows in “The Voice US” and “The Voice Vietnam” in 2012.